The strength of motivation for medical school: A three-year longitudinal study. (2nd September 2021) - An, Min; Li, Liping
Abstract: Based on longitudinal data collected in a sample of Chinese medical students, this study tested the measurement invariance of the strength of motivation for medical school framework and examined the growth trajectories of their motivation for medical school over time. Results revealed that the strength of motivation for medical school scale demonstrated longitudinal measurement invariance. Medical students in our sample showed an overall decline over time in all three types of motivation for medical school. Most of the drop occurred during the first year of medical study. Individual variability was observed in the initial levels and the growth rates of motivation for medical school. We advised medical educators to provide sustained support to help medical students (especially for those early in medical school) improve their learning experience.